Lifetime Halal Certificate Policy: Implications and Challenges for Consumer Protection - Farid Wajdi (Indonesian Journal Education, 2025)
The lifetime halal certificate policy stipulated in the amendment to Law Number 33 of 2014 concerning Halal Product Assurance (Law on Halal Product Assurance) thru Law Number 6 of 2023 concerning Job Creation has sparked controversy among business actors, certification bodies, and the public. On the one hand, this policy is seen as a form of deregulation that promotes efficiency and ease of doing business; on the other hand, it raises concerns about the declining effectiveness of halal supervision and consumer protection guaranties. This research aims to analyze the implications and challenges of the lifelong halal certificate policy from a consumer protection perspective, using a normative legal approach based on Philipus M. Hadjon's legal protection theory and Satjipto Rahardjo's progressive law principles. The research results indicate that without periodic evaluation and verification mechanisms, lifetime halal certificates have the potential to create a false sense of security for consumers and reduce public trust in the national halal assurance system.